Re-creation of a scientific feat - V. I. Ponomarev (Сибирский лесной журнал, 2024)
A review of the contents, processes of writing and reconstitution from manuscript materials of V. P. Grechkin’s monograph «Lesopathological characterization of the forests of the USSR by separate natural and geographical zones» is presented. Edited by Yu. I. Gninenko. In 3 volumes. VNIILM, 2019–2021.